1970
DOI: 10.3329/bjpt.v14i2.535
|View full text |Cite
|
Sign up to set email alerts
|

New records of phytoplankton for Bangladesh: <i>Phacus</i>, <i>Lepocinclis</i> and <i>Pteromonas</i>

Abstract: Not available. Key words: New records, Phytoplankton, Lepocinclis, Phacus, Pteromonas DOI: 10.3329/bjpt.v14i2.535 Bangladesh J. Plant Taxon. 14(2): 167-169, 2007 (December)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As a consequence of these studies, the total number of taxa have increased in Turkey (Taşkın et al, 2019;Maraşlıoğlu & Gönülol, 2020). Similar studies were done and new records were recorded in different parts of the world (Khondker et al, 2006;Alfasane & Khondker, 2007;Oliveira et al, 2013;Bartozek et al, 2018;Akhtar et al, 2019).…”
Section: Introductionmentioning
confidence: 54%
“…As a consequence of these studies, the total number of taxa have increased in Turkey (Taşkın et al, 2019;Maraşlıoğlu & Gönülol, 2020). Similar studies were done and new records were recorded in different parts of the world (Khondker et al, 2006;Alfasane & Khondker, 2007;Oliveira et al, 2013;Bartozek et al, 2018;Akhtar et al, 2019).…”
Section: Introductionmentioning
confidence: 54%
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the members of Euglenophyceae have been made from different fresh water of habitats of Sylhet Division of Bangladesh. So far, there are large number of taxonomic studied of different species of Euglenophycean members were reported (Alfasane and Khondker, 2007;Alfasane et al 2010;Gani et al 2012. Khondker andAlfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981).…”
Section: Introductionmentioning
confidence: 99%